Research progress of breast cancer surgery during 2010–2024: a bibliometric analysis - Kang, Jiawei; Jiang, Nan; Shataer, Munire; Tuersong, Tayier (Frontiers in Oncology, 2024)
PurposeThis study seeks to systematically analyze the research literature pertaining to breast cancer surgery from 2010 to 2024, as indexed in the PubMed database, employing bibliometric methodologies.MethodsEmploying the “bibliometrix” package in the R programming language, alongside VOSviewer and CiteSpace software, this research conducted a comprehensive visual analysis of 1,195 publications. The analysis encompassed publication trends, collaborative networks, journal evaluation, author and institutional assessments, country-specific analyses, keyword exploration, and the identification of research hotspots.ResultsThe study observed a rising trend in the number of publications related to breast cancer surgery. However, there was a concomitant decline in citation rates, potentially indicating either a saturation of the research field or a diminution in research quality. The United States, China, and Japan are the leading contributors to research output, with the United States showing the most extensive international collaboration. The University of California, University of Toronto, and University of Texas MD Anderson Cancer Center were the top institutions for the number of published papers. Through a comprehensive analysis of keywords, we have identified “breast cancer” “pain” “anxiety” “lymphedema” “mastectomy” and “surgery” as central research themes within this domain, the corresponding clusters were subjected to analysis.ConclusionThis study provides a comprehensive review of breast cancer surgery research, emphasizing major research areas and proposing future research directions. This study provides a significant resource for researchers and clinicians in the field.